History of secondary minerals discovered in Jachymov (Joachimsthal) - Veselovsky,F.; Ondrus,P.; Hlousek,J. (Journal of the Czech Geological Society, 1997)
Jachymov is type locality for 22 minerals, including 17 secondary minerals. Data on history of discovery and description of new minerals was extracted by search in old literature. Minerals are arranged in the chronological sequence of discovery. Explanation of names of discredited or re-defined minerals and some historical names is included at the end of this paper.
Keywords: secondary minerals; history description; old mineral names; Jachymov